Modelo experimental de comportamento agressivo utilizando animais da espécie Gallus gallus - Farias, Johann Soares de (2016)
Aggressive behavior constitutes any action that either threatens or leads to or cause, destruction or damage to another organism. Agressive behavior has seen as an adaptive response, which is important to the evolution of the species. Several aggressive behavior models are used, however in most of them, the animals used have gone through domestication, which reduced markedly the aggressive behavior. Some male’s birds from Gallus gallus species can produce intraspecific aggressive responses innately. The present study evaluates the Gallus gallus aggressive behavior, intending to create an animal aggressive behavior model. Adult Gallus gallus weighting between 2.5 and 3.5 kg were used, the animals were placed in the arena measuring 2.0 m² and evaluated for 5 min. Animals were tested for their ability to elicit aggressive behavior. The animals were placed in front of inert stimuli: mirror or stuffed rooster, or the animals were divided in pairs and were placed in front of translucid plastic cylinder or frame, which allowed visual but non-physical contact. The data were analyzed by ANOVA repeated measures test where they were considered significant when p <0.05 and thus, the Tukey test post was performed. The animals expressed pecks and jumps as aggressive behaviors. The mirror test showed a significant reduction in jumps, on day 5. The Stuffed Rooster test did not present statistical difference of expression of the studied behavior across the time. The Cylinder test when the analyzed rooster was free in the arena and the Frame test did not show statistical difference and maintained the expression of aggressive behavior. Placing the rooster inside the cylinder, reduced numbers of jumps. Comparison between type of test showed that animals tested in Mirror or Stuffed Rooster tests have fewer jumps than the other groups. Additionally, the stuffed rooster test shows less pecking behavior the other groups. Our study showed that the main aggressive behaviors expressed by Gallus gallus animals were pecks and jumps. Also, the reaction from another rooster is important to maintenance of the aggressive behavior across successive tests. Based in results from current study we propose that the Cylinder test when the rooster positioned outside it and the frame test are most appropriate models to evaluate aggressive behavior in Gallus gallus.